1998
DOI: 10.1021/jf980113q
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Atom Induced Room Temperature Phosphorescence Method for the Determination of the Plant Growth Regulator β-Naphthoxyacetic Acid

Abstract: A simple, selective, and sensitive heavy atom induced room temperature phosphorimetric method (HAI-RTP) is described for the determination of the plant growth regulator β-naphthoxyacetic acid (NOA) in spiked apple samples. A careful selection of the different variables (heavy atom and sodium sulfite) to obtain the phosphorescence signal constitutes the basis of a HAI-RTP method for the determination of NOA. The analytical curve of NOA gives a linear dynamic range of 0−625 ng mL-1 and a detection limit of 30.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In the 70s and 80s, direct fluorescence analysis, without any previous chromatographic separation, was used for the determination of ␣-NAA and NAD [8,9]. Afterwards direct phosphorescence was also employed not only for the acid and the amide but also for ␤-NOA [10][11][12][13]. Once the chromatographic techniques became more significant in method development, reversed-phase liquid chromatography using C18 columns was employed for the analysis of these compounds using UV or fluorescence spectroscopy as detection techniques [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In the 70s and 80s, direct fluorescence analysis, without any previous chromatographic separation, was used for the determination of ␣-NAA and NAD [8,9]. Afterwards direct phosphorescence was also employed not only for the acid and the amide but also for ␤-NOA [10][11][12][13]. Once the chromatographic techniques became more significant in method development, reversed-phase liquid chromatography using C18 columns was employed for the analysis of these compounds using UV or fluorescence spectroscopy as detection techniques [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…NAD has been widely used in agriculture for more than 60 years as a component in many commercial plant rooting and horticultural formulations . It is used: (1) as fruit thinning agent for a variety of fruits such as apple, pear, peach, grape; (2) for root cuttings; and (3) to prevent fruit drop shortly before harvest . Its action mainly involves inducing abscission of flower buds.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies [10] have demonstrated that RTP emission of some compounds can be directly induced in aqueous solutions assisted only by addition of relatively high concentrations of a heavy atom perturber and sodium sulfite as chemical deoxygenator [11,12,13,14,15,16,17,18,19]. This type of RTP emission has been called heavy atom induced -room temperature phosphorescence (HAI-RTP) [10,11,12,13,14,15,16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This type of RTP emission has been called heavy atom induced -room temperature phosphorescence (HAI-RTP) [10,11,12,13,14,15,16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%